Linguistic representation of disharmony of life in “The Cherry Orchard” by A. Chekhov and “Reserve” by S. Dovlatov - Gazarova, Diana (Bulletin of Yerevan University H: Russian Philology, 2022)
The article examines the works of two authors: A. Chekhov and S. Dovlatov. Various literary critics noted the similarity of the Dovlatov’s and Chekhov’s methods of constructing the literary text, the combination of the comic and the dramatic in their works, laconicism, the use of elements of the poetics of the absurd. The article examines works of different genre - the play by A. Chekhov “The Cherry Orchard” and the story by S. Dovlatov “Reserve”. The linguistic ways of expressing the disharmony of life and psychological imbalance of the characters are analyzed in the article: antonymy, explicit and implicit deny, adversative conjunctions. All the examined linguistic techniques emphasize the isolation, "otherness" of the spaces depicted by the authors, their opposition to another life that takes place outside the garden and the reserve. However, this opposition is not a confrontation, but a comparison, a combination of incompatible, coexistence based on the psychological imbalance of the heroes of these works of different genre, but united by a common idea.
Keywords: “The Cherry Orchard”; “Reserve”; antonyms; adversative conjunctions; explicit deny; implicit deny; disharmony of life; psychological imbalance